TIKTOK SOCIAL MEDIA INSIGHTS IN DIGITAL MARKETING - Masayu, Shafira Alfi; Prasojo, Bayu Hari; Yulianto , Mochamad Rizal; Racmadany , Andry (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The development of technology and social media has changed the dynamics of digital marketing, with TikTok as one of the most prominent platforms. This article discusses insights into TikTok's use in digital marketing, highlighting how the platform offers a new approach to engaging with audiences. Method: This research uses qualitative methods to analyze data from various sources. Results: Through its For You Page (FYP) algorithm, TikTok leverages user behavior data to deliver relevant content, increasing engagement and brand reach. The TikTok Live feature provides opportunities for businesses, especially MSMEs, to interact directly with consumers, strengthening promotional strategies through real-time interactions. In addition, collaboration with influencers and personalized content has proven effective in increasing brand awareness and purchase intent. The results confirm the importance of creative and interactive content in attracting users' attention and encouraging them to make purchases. Novelty: TikTok offers a new approach to engaging with audiences by leveraging user behavior data and real-time interaction features, presenting unique advantages for businesses to boost brand awareness and drive purchase intent through creative, personalized content strategies.